Attorney fraud in the law firm: a case study of crime convenience theory and crime signal detection theory - Asting, Cecilie (Deviant behavior, 2023)
This article starts with a brief review of law firm business. Next, crime convenience theory is applied to the case by identifying relevant convenience themes for financial motive, organizational opportunity, and personal willingness. Then, a brief application of crime signal detection theory is presented. In the discussion, governance in the form of restrictions based on convenience theory is discussed. Prevention and detection of wrongdoing is at the core of governance to secure compliance with laws, regulations, rules, and guidelines. The lack of transparency among stakeholders in the case of the law firm is detrimental to governance. The discourse and rituals of transparency, account-giving, and verification are central to governance.